2014
DOI: 10.4103/0974-7796.134254
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of naftopidil and tamsulosin in the treatment of patients with lower urinary tract symptoms with benign prostatic hyperplasia

Abstract: Introduction:Naftopidil, approved initially in Japan, is an α1d-adrenergic receptor antagonist (α1-blocker) used to treat lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH). It is different from tamsulosin hydrochloride and silodosin, in that it has a higher affinity for the α1D-adrenergic receptor subtype than for the α1A subtype and has a superior efficacy to a placebo and comparable efficacy to other α1-blockers such as tamsulosin. The incidences of ejaculatory disorders and intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Differences among α1-adrenoceptor blockers with respect to the degree of efficacy in male LUTS have been controversial. Gotoh et al reported that naftopidil is as effective as tamsulosin on the symptom basis using the International Prostate Symptom Score [26,27]. Nishino et al [28] reported that maximum desired volume and first desired volume were higher with naftopidil than with tamsulosin in a pressure flow study.…”
Section: Discussionmentioning
confidence: 99%
“…Differences among α1-adrenoceptor blockers with respect to the degree of efficacy in male LUTS have been controversial. Gotoh et al reported that naftopidil is as effective as tamsulosin on the symptom basis using the International Prostate Symptom Score [26,27]. Nishino et al [28] reported that maximum desired volume and first desired volume were higher with naftopidil than with tamsulosin in a pressure flow study.…”
Section: Discussionmentioning
confidence: 99%
“…Naftopidil has a 3 fold higher affinity for the α1DARsubtype than for the α1A-AR subtype, and naftopidil shows different effects on lower urinary tract symptoms because many α1D-ARs exist in the bladder neck [ 17 ]. Both α1-AR subtype antagonists alleviate bladder outlet obstruction symptoms, such as residual urine and urinary urge sensation, by reducing the prostate size [ 18 ]. Overactive bladder symptoms, including frequency, urgency, nocturia, and urgency incontinence, were decreased by α1-AR antagonists in clinical and animal studies [ 12 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, naftopidil has a 3-fold affinity for the α 1 D-AR subtype rather than the α 1 A-AR subtype, and naftopidil shows different characteristics on LUTS, because major α 1 DAR exists in the bladder neck [10]. Both α 1 -AR subtype antagonists alleviate OAB-related symptoms, such as frequent micturition and urinary urge sensations [11]. Frequency, urgency, nocturia, and urgency incontinence were decreased by α 1 -AR antagonists in clinical research [12].…”
Section: Discussionmentioning
confidence: 99%